National Library of Indonesia Collection and Early Cold War: Case Study of United States Information Service (USIS) Bulletin (1948-1953) - Frial Ramadhan Supratman (Universitas Airlangga, 2023)
ABSTRACT Cold War was a war which does not merely involved military and economic aspects. The war also involved several aspects, including information media, such as newspaper, magazine, movie etc. Although Cold War was ended up by the fall of Soviet Union in 1991, however, the memory of Cold War is still preserved in library collection. National Library of Indonesia is the center of national deposit preserving all of Indonesia-based publications since colonial era until present day. One of Cold War collection deposited in the National Library is United States Information Service (USIS) Daily Bulletin. The collection is deposited in the division of rare newspaper collection, National Library of Indonesia. This article investigates history and analysis of content information regarding USIS Daily Bulletin from historical and library science perspective. Method used in this article is qualitative method by analyzing document through international history perspective. The aim of this research is to know information content of National Library of Indonesia’s collection in Cold War era Accordingly, author argues that USIS Daily Bulletin is the National Library’s collection containing culture and poltical propaganda of United States of America (USA) in early Cold War era. Keywords: United States Information Service (USIS); Cold War; National Library of Indonesia; Information, Newspaper. Koleksi Perpustakaan Nasional RI dan Perang Dingin Awal: Studi Kasus United States Information Service (USIS) Bulletin (1948-1953) ABSTRAK Perang Dingin merupakan perang yang tidak hanya melibatkan kekuatan militer dan ekonomi saja. Perang ini banyak melibatkan berbagai aspek, termasuk media informasi, seperti surat kabar, majalah, film dan lain-lain. Meskipun Perang Dingin sudah berakhir pada 1991 yang ditandai dengan keruntuhan Uni Soviet, namun memori mengenai Perang Dingin masih tersimpan di dalam koleksi perpustakaan. Perpustakaan Nasional Republik Indonesia (RI) merupakan pusat deposit nasional yang menyimpan seluruh terbitan Indonesia sejak era kolonial Belanda hingga hari ini. Salah satu koleksi Perang Dingin yang tersimpan di Perpustakaan Nasional adalah United States Information Service (USIS) Daily Bulletin. Koleksi ini tersimpan di divisi surat kabar langka, Perpustakaan Nasional RI. Artikel ini membahas mengenai sejarah dan analisis konten informasi dari USIS Bulletin dari perspektif ilmu sejarah dan perpustakaan. Metode yang digunakan di dalam artikel ini adalah metode kualitatif dengan melakukan analisis dokumen menggunakan perspektif sejarah internasional. Tujuan dari penelitian ini adalah untuk mengetahui konten informasi dari koleksi Perpustakaan Nasional RI pada era Perang Dingin. Berdasarkan hal tersebut, penulis berargumen bahwa USIS Daily Bulletin merupakan koleksi Perpustakaan Nasional yang memuat propaganda kebudayaan dan politik Amerika Serikat (AS) untuk menanamkan pengaruh di Indonesia pada era Perang Dingin awal. Kata kunci: United States Information Service (USIS); Perang Dingin; Perpustakaan Nasional RI; Informasi; Surat Kabar.